VIIIth international congress on the economic and social history of Turkey, June 18-21, 1998, Bursa : papers = VIII. Uluslararası Türkiye’nin sosyal ve ekonomik tarihi kongresi, 18-21 Haziran 1998, Bursa : bildiriler (Morrisville)
322 s.